La imagen de Hungría en el cine franquista - Lénárt, András (Acta Hispanica, 2014)
The complex relationship between film and history represents a thoughtprovoking interdisciplinary research field. The formation of a suitable film policy constituted a substantial assignment in all European dictatorships of the 20th century. Among them, the cinema of Francisco Franco’s regime was one of the most interesting examples. The Spanish general considered that communism was the most dangerous and a genuinely diabolical enemy of the Christian civilization. In compliance with this obsession, the regime’s film industry produced quite a few movies that backed the dictator’s deep-rooted anticommunism. Hungary, a Central European country under communist rule, also belonged to this paradigm: Hungarian topics, events and individuals appeared every now and then in those films that discussed the drawbacks and horrors of being part of the Soviet block. In this paper I analyze three Spanish propaganda movies from the 1950’s where Hungary and Hungarians played a central role.